Increased incidence of cancer in first degree relatives of women with double primary carcinomas of the breast and colon. Issue 7 (July 1996) - Foulkes, W D; Bolduc, N; Lambert, D; Ginsburg, O; Olien, L; Yandell, D W; Tonin, P N; Narod, S A
Abstract : Breast and colon cancer are among the most common cancers in the developed world. Several epidemiological studies suggest that the occurrence of one of these two cancers in a woman may predispose to the development of the other. The occurrence of both forms of cancer in the same woman may be because of chance or common susceptibility. In order to determine how frequently double primary cancers have a hereditary basis, we conducted a registry based study at a single Montreal hospital. Cancer rates in first degree relatives of patients with multiple primaries were compared with provincial age standardised incidence rates and relative risks (RRs) were estimated. In first degree relatives under 45 there was a total of 15 cancers observed, compared with 3.70 expected, giving an RR of 4.05 (95% CI: 2.27-6.68). The RR for colon cancer was significantly increased among male relatives. For relatives less than 45 years old at diagnosis, the RR for colon cancer was 66.7 (95% CI: 13.8-195) (three cases observed, 0.045 expected). For all ages the RR was 5.02 (95% CI: 2.04-10.5). The RR for breast cancer was 5.92 (95% CI: 1.91-13.8) for female relatives under 45 (five cases observed, 0.845 expected) and 2.14 (95% CI: 1.07-3.83) for breast cancer at any age. These results suggest that there may be genes that predispose to both breast and colon cancer in certain people.